2023
DOI: 10.1590/fst.117022
|View full text |Cite
|
Sign up to set email alerts
|

NMR-based metabolic analysis of Bacillus velezensis DZ11 applied to low-salt fermented coarse fish involved in the formation of flavor precursors

Abstract: Microbial fermentation can be responsible for flavor production and increasing the nutritional quality of fermented fish foods. The study aimed to isolate non-halophilic bacteria possessing proteolysis and lipolysis properties as starter cultures for low-salt content fermentation of coarse fish. The strains with high enzyme activities were screened and multiple growth characteristics were analyzed. The content of amino acid nitrogen and trichloroacetic acid (TCA)-soluble peptides in fermented fish was also inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Particularly, as the important precursors of flavor compounds, branched-chain amino acids (valine, leucine, and isoleucine) and sugar (gluceptate, UDP-D-galactose, UDP-glucose etc.) could potentially enrich the flavor of products [48] .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, as the important precursors of flavor compounds, branched-chain amino acids (valine, leucine, and isoleucine) and sugar (gluceptate, UDP-D-galactose, UDP-glucose etc.) could potentially enrich the flavor of products [48] .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the flavor of bean paste was related to B. velezensis fermentation [15] . B. velezensis DZ11 improved the flavor of low-salt fermented coarse fish [16] . T h e p r o t e a s e -p r o d u c i n g s t r a i n s B .…”
Section: Introductionmentioning
confidence: 99%